Bifidobacterium lactis 420 and fish oil enhance intestinal epithelial integrity in Caco-2 cells - Kati Mokkala; Kirsi Laitinen; Henna Röytiö (Elsevier, 2022)
Increased intestinal permeability is a predisposing factor for low grade inflammation-associated conditions, including obesity and type 2 diabetes. Dietary components may influence intestinal barrier integrity. We hypothesized that the dietary supplements Bifidobacterium lactis 420, Lactobacillus rhamnosus HN001, and fish oil have beneficial impacts on intestinal barrier integrity. In addition, we hypothesized that the co-administration of these components results in synergistic benefits to the integrity of the intestinal barrier. To study this, we investigated the impact of cell free culture supernatant from dietary supplements B. lactis 420 and L.rhamnosus HN001, and fish oil; separately and in combination, on intestinal permeability in a CaCo-2 cell model. Administered separately, both B. lactis 420 supernatant and fish oil significantly increased the integrity of the intestinal epithelial barrier, as determined by an increase in transepithelial electrical resistance (TEER), whereas L. rhamnosus did not. The TEER increase with B. lactis 420 was dose dependent. Interestingly, a combination of B. lactis 420 supernatant and fish oil negated the increase in TEER of the single components. mRNA expression of tight junction proteins, measured by real time qPCR, was not altered, but the mRNA expression of myosin light chain kinase (MLCK) increased after fish oil treatment. To conclude, single dietary components, namely B. lactis 420 and fish oil induced beneficial effects on intestinal barrier integrity in vitro, whilst a combination of two beneficial test compounds, resulted in a null effect.